Harnessing the DNA Dye-triggered Side Population Phenotype to Detect and Purify Cancer Stem Cells from Biological Samples - Boesch, Maximilian (J Vis Exp, 2017)
Cancer is a stem cell-driven disease and eradication of these cells has become a major therapeutic goal. Deciphering vulnerabilities of Cancer Stem Cells (CSCs) and identifying suitable molecular targets relies on methods that allow their specific discrimination in heterogeneous samples such as cell lines and ex vivo tumor tissue. Flow cytometry/FACS is a powerful technology to multi-parametrically dissect biological samples at the single cell level and is to date the method of choice to recover live cells for downstream analyses. Surface markers such as CD44 and CD133 as well as detection of aldehyde dehydrogenase enzymatic activity have often been used to define and sort out CSCs from tumor samples by FACS. A complementary approach, depicted here in methodological detail, makes use of functional dye extrusion by ABC drug transporters, which identifies a distinct population of fluorescence-dim cells commonly referred to as side population (SP). SP cancer cells exhibit canonical stem cell characteristics and can be abrogated and functionally confirmed using agents that inhibit the dye-extruding drug transporter (most frequently ABCB1/P-glycoprotein/MDR1/CD243 and ABCG2/Bcrp1/CD338). Moreover, the SP assay is compatible with other flow cytometric evaluations such as staining of surface antigens, aldehyde dehydrogenase detection and dead cell discrimination (e.g., with 7-AAD or propidium iodide (PI)). Thus, we describe a valuable and broadly applicable method for CSC identification, isolation and sub-characterization mechanistically based on a functional, rather than a phenotypic parameter. Although originally performed with Hoechst 33342 as triggering dye, we here focus on the more recent Violet dye-based SP phenotype that is resolvable on any flow cytometer equipped with a violet laser source.